Superior lentiviral vectors designed for BSL-0 environment abolish vector mobilization. Issue 7 (October 2018) - Hu, Peirong; Bi, Yanmin; Ma, Hong; Suwanmanee, Thipparat; Zeithaml, Brian; Fry, Nate; Kohn, Donald; Kafri, Tal
Abstract Lentiviral vector mobilization following HIV-1 infection of vector-transduced cells poses biosafety risks to vector-treated patients and their communities. The self-inactivating (SIN) vector design has reduced, however, not abolished mobilization of integrated vector genomes. Furthermore, an earlier study demonstrated the ability of the major product of reverse transcription, a circular SIN HIV-1 vector comprising a single- long terminal repeat (LTR) to support production of high vector titers. Here, we demonstrate that configuring the internal vector expression cassette in opposite orientation to the LTRs abolishes mobilization of SIN vectors. This additional SIN mechanism is in part premised on induction of host PKR response to double-stranded RNAs comprised of mRNAs transcribed from cryptic transcription initiation sites around 3'SIN-LTR's and the vector internal promoter. As anticipated, PKR response following transfection of opposite orientation vectors, negatively affects their titers. Importantly, shRNA-mediated knockdown of PKR rendered titers of SIN HIV-1 vectors comprising opposite orientation expression cassettes comparable to titers of conventional SIN vectors. High-titer vectors carrying an expression cassette in opposite orientation to the LTRs efficiently delivered and maintained high levels of transgene expression in mouse livers. This study establishes opposite orientation expression cassettes as an additional PKR-dependent SIN mechanism that abolishes vector mobilization from integrated and episomal SIN lentiviral vectors.